EDUCATION OF HEALTHY MEAL BOX AT SDN 02 BRUBUH - Rooiqoh, Qothrunnadaa Fajr; Karomi, Kholid; Qurroti, A’yun; Matdoan, Maulidia Mahmudah; Nabilah, Yumna Amirotin; Hilaliah, Dini Dzulfa; Islami, Merdina; Salbila, Ahda; Dewi, Sundari Fortuna; Rana, Annisa; Najiebah, Arwa; Jannah, Hani’atu Anharil (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This research aims to evaluate the effectiveness of healthy food education and health outreach at SDN 2 Brubuh, which was carried out through a healthy and nutritious creative meal box competition. The outreach method involves conveying information about the importance of healthy food and good health practices to students, while creative meal box competitions provide an interactive means of strengthening this understanding. Apart from that, the practice of washing hands with soap is also implemented as an integral part of health outreach. This research involved 70 students from various grade levels at SDN 2 Brubuh. The results showed a significant increase in students' health understanding and practices after implementing the activities, with a marked increase in healthy food choices and compliance with hand washing practices. These findings indicate that health education and health outreach through creative meal box competitions can be an effective approach in increasing students' health awareness and behavior in the school environment.